(untitled) (Novos Olhares, 2018)
In this article, we propose a re-reading of the film The Terminal (StevenSpielberg, 2004), highlighting points that approximate it to discussions abouttime, space, place and non-place, through the perspectives of some authors. Wesee the film based on the concept of the outsider (Schutz, 2003), the one who is aforeigner in a certain time and space. With this, we seek to bring up aspects thatallow us to think about everyday life within these dimensions.